Electrical Analysis Using ESP-32 Module In Realtime - Erik Wahyu Pratama; Agus Kiswantono (Fakultas Teknik Universitas Bhayangkara, 2022)
Microcontroller is a core part of the control GUI project. The choice of microcontroller is very influential on the results of data processing on the system. On the basis of these thoughts, a study was conducted which aims to find a microcontroller with good data processing capabilities. In this study using the ESP32 microcontroller microcontroller. Where the microcontroller has different specifications. the ESP32 microcontroller produces an average voltage error value of 0.312182825 percent and a current of 0.194657573 percent.